Modelling transformational and transactional leadership, innovation and performance in selected South African Universities of Technology: a balanced scorecard perspective. - Mofokeng, G. L. (Vaal University of Technology, 2022)
Universities of Technology are an essential institutional type in South African higher education. However, their performance often lags behind that of traditional and comprehensive universities, which inspires the need to use research to seek ways of improving them. This study focuses on the interconnection between transformational and transactional leadership, organisational innovation and performance in South African universities of technology. Performance was measured based on the balanced scorecard perspective. The study followed a quantitative method, using the views of 387 academic and non-academic professional respondents drawn from three South African universities of technology. Hypotheses were tested using correlations and regression analysis. The study identified three transformational leadership factors, namely idealised influence, intellectual stimulation and inspirational leadership that are relevant to the tested relationship. Six performance dimensions, namely internal growth, financial performance, internal processes, customer satisfaction, learning, and grants and income were also identified and used to measure performance. The three transformational leadership factors, idealised influence, intellectual stimulation and inspirational leadership all correlated with and predicted innovation. In turn, innovation correlated with and predicted the six performance factors (internal growth, financial performance, internal processes, customer satisfaction, learning, and grants and income). The study indicates that the transformational leadership style has a direct positive effect on institutional innovation in universities of technology. Furthermore, innovation is an important driver of performance. Therefore, universities of technology that place an emphasis on transformational leadership and innovation are likely to register superior performance.
Ph. D. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Transformational leadership; Transactional leadership; Innovation; Performance; University of Technology; Higher Education; Organisational innovation; Balance scorecard perspective; Dissertations, Academic -- South Africa.; Management -- Study and teaching (Higher).; Transformational leadership.; Organizational change.